A facile synthesis of a cobalt nanoparticle–graphene nanocomposite with high-performance and triple-band electromagnetic wave absorption properties. Issue 3 (3rd January 2018) - Long, Qin; Xu, Zhiqiang; Xiao, Huanhuan; Xie, Kenan
Abstract : Ferromagnetic metal nanoparticle/graphene nanocomposites are promising as excellent electromagnetic (EM) wave absorption materials. Abstract : Ferromagnetic metal nanoparticle/graphene nanocomposites are promising as excellent electromagnetic (EM) wave absorption materials. In this work, we used a facile method to synthesize a cobalt nanoparticle–graphene (CoNP–G) nanocomposite. The obtained CoNPs–G exhibited a saturation magnetization ( M s ) of 31.3 emu g −1 and a coercivity ( H C ) of 408.9 Oe at 298.15 K. In particular, the CoNPs–G nanocomposite provided high-performance EM wave absorption with multiband, wide effective absorption bandwidth, which was mainly attributed to the synergy effects generated by the magnetic loss of cobalt and the dielectric loss of graphene. In the range of 2–18 GHz, the sample (55 wt% CoNPs–G) held three effective reflection loss (RL) peaks (frequency ranges of 2.4–3.84, 7.84–11.87 and 13.25–18 GHz, respectively, RL ≤ −10 dB) with the coating thickness of 4.5 mm, and the effective bandwidth reached the maximum of 10.22 GHz, and the minimal RL reached −40.53 dB at 9.50 GHz. Therefore, the CoNPs–G nanocomposite presents a great promising application in the electromagnetic wave absorption field.